The Analysis of Speech Perception with the Use of Hearing Protection Earplugs using the Canadian Digit Triplet Test - El Mawazini, Ahmed; Giguère, Christian (Canadian Acoustics, 2023)
One of the primary contributors to hearing loss is noise. When the daily noise exposure exceeds 85 dBA over a duration of 8 hours, workers need to wear hearing protection to protect themselves against the effects of noise exposure. However, workers in noisy work environments are often reporting difficulties with speech perception when using hearing protection equipment, especially those with pre-existing hearing loss. This poses a dilemma for workers as they need hear important sounds in their work environment and communicate verbally with their colleagues while effectively protecting themselves from loud noises. A pilot doctoral research project was conducted at the University of Ottawa to study this issue. This project aimed at comparing the attenuation produced by earplugs among participants with normal hearing and those with hearing loss in relation to the instructions given to participants on how to fit their earplugs. This pilot project also strived to analyse speech perception with the use of earplugs in both participant groups using the Canadian Digit Triplet Test (CDTT) as a function of the amount of attenuation achieved. The attenuation provided by earplugs was similar between participants with normal hearing and those with hearing loss. Preliminary results also demonstrated that speech becomes harder to perceive when participants wore their earplugs, especially when given instructions on how to fit them properly. In some participants with hearing loss, earplug attenuation leads to an increase in auditory thresholds to a level where simple speech material like digit strings may no longer be audible at normal vocal levels (55-60 dBA). This can pose a safety risk for workers with hearing loss in some situations, as they may be unable to comprehend essential workplace messages due to the additional hearing difficulties induced by the earplugs.